UPAYA PENINGKATAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA MELALUI PENGGUNAAN MEDIA GAMIFIKASI BERBASIS REALITA DI KELAS VI SDN GEMPOLSONGO - Cahyani, Anisah Indriana; Hindriana, Putri Tiara; Ermawati, Diana (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2024)
The purpose of this study is to detail how sixth graders at SDN Gempolsongo used gamification media based on real-world elements to enhance their scientific understanding of the four basic energy sources: heat, electricity, light, and sound. Classroom action research is used as a descriptive approach (PTK). Sixth graders (eight males and eight females) and their instructors made up the sample for this study. Assessments and observation sheets are used in data collecting procedures. Quantitative descriptive analysis is put to use for the data analysis. Teachers' and students' capacities for learning outcome planning and implementation are both enhanced by the study. Finally, student learning outcomes are improved by using gamification media based on reality.